2012
DOI: 10.1021/ja3065649
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Chemical Pressure Effects in Single-Component Molecular Metals Based on Radical Dithiolene and Diselenolene Gold Complexes

Abstract: On the basis of the reported radical neutral complex [Au(Et-thiazdt)(2)] (Et-thiazdt = N-ethyl-1,3-thiazoline-2-thione-4,5-dithiolate), a series of single-component conductors derived from [Au(Et-thiazdt)(2)], also noted as [AuS(4)(═S)(2)], has been developed, by replacing the outer sulfur atoms of the thiazoline-2-thione rings by oxygen atoms and/or by replacing the coordinating sulfur atoms by selenium atoms toward the corresponding diselenolene complexes. Comparison of the X-ray crystal structures and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
84
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 67 publications
8
84
1
Order By: Relevance
“…Earlier ab initio calculations have shown indeed that electron−electron repulsions are able to open a Mott−Hubbard gap in these systems, providing a rationale for the observed Mott insulator character. 11,12 The reference complex [Au(Et-thiazdt) 2 ] was found with a very small Mott−Hubbard gap and was sensitive to the pressure, becoming metallic above 1. In conclusion, these neutral radical gold complexes provide an extensive series of single-component conductors whose solid-state organization, and associated electronic properties, proved highly sensitive to minute structural modifications.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier ab initio calculations have shown indeed that electron−electron repulsions are able to open a Mott−Hubbard gap in these systems, providing a rationale for the observed Mott insulator character. 11,12 The reference complex [Au(Et-thiazdt) 2 ] was found with a very small Mott−Hubbard gap and was sensitive to the pressure, becoming metallic above 1. In conclusion, these neutral radical gold complexes provide an extensive series of single-component conductors whose solid-state organization, and associated electronic properties, proved highly sensitive to minute structural modifications.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…11 We have also demonstrated that, through small modifications of the dithiolate ligand, it is also possible to impact the conducting properties (and their pressure dependence) by exercising not only a physical pressure but also a chemical pressure. 12 Actually, this was realized by replacing either the exocyclic sulfur atom by an oxygen atom, as in [Au(Et-thiazodt) 2 ] • , or by substituting the coordinated sulfur atoms of the metallacycles for selenium atoms. These compounds were all isostructural, allowing for a useful comparison of their electronic structures, because the chemical pressure effects identified then proved indeed highly anisotropic.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In principle, the functionalization of the ligands with appropriate substituents should increase the solubility of these neutral complexes. Indeed, high conductivity and even metallic properties under pressure have been found recently in neutral gold complexes with the N ‐ethyl‐2‐thioxo‐1,3‐thiazoline‐4,5‐dithiolate ligand16 and in the corresponding selenium analogues,17 which are fairly soluble as they have peripheral ethyl groups. In this work, we have prepared and characterised a new family of thiophenedithiolene transition metals complexes based on a new ligand, 5‐methylthiophene‐2,3‐dithiolate (α‐mtpdt).…”
Section: Introductionmentioning
confidence: 98%
“…19 2 ] lacking one electron, could offer a very attractive playground to evaluate the effect of alloying on the conducting and magnetic properties of (single-component) molecular conductors. For that purpose, it can be important (but not a stringent requirement) that both gold and nickel complexes are isostructural.…”
Section: ■ Introductionmentioning
confidence: 99%